Predatory Pricing: Persaingan Harga Minimarket dan Gadde-Gadde dalam Metafora Cerpen - Andi Sri Wahyuni (Jurnal Akuntansi Multiparadigma, 2015)
This article is aimed to explore the determination of agressive cost of product (predatory pricing) used by minimarket. Short story metaphor by Eka Kurniawan, “Kisah Seorang Kawan” as methodology. The “father” figure in this story has similiar condition with enterpreneur of gadde-gadde. The story begins with the attendant of “the rich merchant” who represent the arrival of minimarket in housing area at Makassar. Through the short story, strategy of predatory pricing could attract customer to move from gadde-gadde to minimarket. Finally, these changes could diminish small businesses which are become the primary economic sector.